The effect of lifetime fluoridation exposure on dental caries experience of younger rural adults. (March 2015) - Crocombe, LA; Brennan, DS; Slade, GD; Stewart, JF; Spencer, AJ
Abstract Background The aim of this study was to confirm whether the level of lifetime fluoridation exposure is associated with lower dental caries experience in younger adults (15–46 years). Methods Data of the cohort born between 1960 and 1990 residing outside Australia's capital cities from the 2004−2006 Australian National Survey of Adult Oral Health were analysed. Residential history questionnaires were used to determine the percentage of each person's lifetime exposure to fluoridated water (<50%/50+%). Examiners recorded decayed, missing and filled permanent teeth (DMFT). Socio‐demographic variables, periodontal risk factors, and access to dental care were included in multivariable least‐squares regression models. Results In bivariate analysis, the higher level of fluoridation category had significantly lower DMFT (mean 6.01 [SE = 0.62]) than the lower level of fluoridation group (9.14 [SE = 0.73] p < 0.01) and lower numbers of filled teeth (4.08 [SE = 0.43], 7.06 [SE = 0.62], p < 0.01). In multivariate analysis, the higher number of full‐time equivalent dentists per 100 000 people was associated with a lower mean number of missing teeth (regression coefficient estimate = –1.75, p = 0.03), and the higher level of water fluoridation with a lower mean DMFT (–2.45, p < 0.01) and mean number of filled teeth (–2.52, p < 0.01). Conclusions The higher level of lifetime fluoridation exposure was associated with substantially lower caries experience in younger rural adults, largely due to a lower number of filled teeth.